Developing an Webquest Media to Improve of Career Choices of SMK Muhammadiyah Cilegon - Solihah, Iis; Purwanta21, Edi (Proceedings of Siliwangi Annual International Conference on Guidance and Counselling, 2022)
There is no denying the increasing role and influence of web technologies in versatile individuals, their independent career choices, professional self-design, and professional skills development. Due to the increasing availability of technology as a vehicle for career information services to increase student career choices, researchers are developing web-based information. This type of research is research and development. This research phase focuses on product manufacturing and development. The stages of development used in this research are (1) needs analysis, (2) information collection through questionnaires and interviews, (3) product design through flow charts and storyboards, and (4). ) The design was verified by two media and material validators, and (5) design modifications were made based on the validator's suggestions. The research subjects were 75 students of class X-XII SMK Muhammadiyah Cilegon. Product in the form of webquest media is effective to increase career choice (p=0.000). There was an increase in the average score of student career selection in the pre-test group of 129.05 and post-test of 150.01 using webquest media.